Usia Ibu dan Hubungannya dengan Kondisi Kehamilan, Persalinan, Postpartum dan Kondisi Neonatal - Hapisah, Hapisah; Rusmilawaty, Rusmilawaty; Sofia, Norlaila; Hipni, Rubiati; Megawati, Megawati (Journal of Telenursing (JOTING), 2024)
This study analyzes the relationship between maternal age and various aspects of pregnancy, delivery, postpartum conditions, and neonatal outcomes in Indonesia. The research method used was an observational design with a cross-sectional approach. The results showed that there was a significant relationship between maternal age and pregnancy conditions (p<0.001) with young mothers (<20 years) showing higher levels of anemia (6.7% vs 3.5%) and KEK (8.8% vs 3.0%) compared to the 20-35 year age group. Postpartum infections were more common in young mothers (20.1% vs 15.2%) although this difference was not statistically significant (p=0.087). Low Birth Weight was higher in babies born to young mothers (4.1% vs 2.1%) but this difference was not statistically significant (p=0.096). This study highlights the impact of maternal age on various aspects of maternal and neonatal health in Indonesia. Young mothers (<20 years) are at higher risk of complications during pregnancy, delivery, and the postpartum period. In conclusion, maternal age has a significant impact on various aspects of maternal and neonatal health in Indonesia. Young mothers (<20 years) are at higher risk for certain pregnancy complications and poor delivery outcomes. Keywords: Pregnancy, Neonatal Condition, Childbirth, Post Partum, Maternal Age